Development of the SWB-HL: A Scale of the Subjective Well-Being of Older Adults With Hearing Loss - Humes, Larry E. (Frontiers in Psychology, 2021)
The objective of this research was to develop and evaluate a self-report measure of subjective well-being (SWB) for use with older adults with hearing loss (HL). A convenience sample of 173 local volunteers between the ages of 60 and 88 years (M= 74.4; SD=7.2 years) participated in this study. The initial 18-item version of the scale was constructed, response characteristics examined, and then subjected to factor analysis, as well as evaluation of the scales' reliability and validity. The analysis of response characteristics and subsequent factor analysis resulted in the elimination of 8 of the 18 test items. The SWB-HL Total score was derived from the 10 remaining items. It was shown that the SWB-HL tapped three underlying domains interpreted as: Life Satisfaction (3 items); Acceptance of Hearing Loss (Accept HL; 4 items); and Social Support (3 items). Psychometric analysis showed very good reliability and good criterion validity was established for the 10-item SWB-HL Total score. In addition, significant differences were observed between aided and unaided SWB-HL Total scores following 4-6 weeks of hearing aid use. The SWB-HL is a 10-item self-report measure of SWB that shows good reliability and validity when used by older adults with hearing loss and reveals improved SWB following the use of hearing aids.